Electrocardiogram Testing in Symptomatic Patient with Type-II Diabetes and Left Ventricular Diastolic Dysfunction - Ali Zulqar Nain, Ambreen Sehar, Mussarat Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main objective of the study is to find the exercise electrocardiogram testing in asymptomatic patient with Type-II diabetes and left ventricular diastolic dysfunction. Methods: This descriptive study was conducted in DHQ Hospital, Sheikhupura during January 2019 to November 2019. The data was collected from 50 patients of type II DM. These all patients has normal electrocardiogram (ECG) and normal systolic function. Result: The data was collected from 50 patients of both genders. The mean age of the patients was 47.83±5.61 years. After getting data the results were divided into two parts. There were 25 patients in group A and 25 patients group B. The mean duration of diabetes is 2.5±5.61 years. There were 20 males and 30 females in this data. There were no significant difference of fasting blood sugar in both groups. There was no statically significant difference between two groups regarding left atrial dimension, aortic root dimension, LV end-diastolic dimension, ejection and LV mass. Conclusion: It is concluded that It is concluded that coronary supply route sicknesses is a typical issue in DM, with diastolic brokenness and increment uniquely in patients with positive pressure practice electrocardiography.